Addressing challenges in the implementation of precision oncology: An in-depth examination of limitations and disparities in the treatment of non-small cell lung cancer in the Brazilian public healthcare system (SUS) - Luma Princess Schneider; Jean Henri Maselli-Schoueri; Barbara de Souza Gutierres Aguiar; Pedro Nazareth Aguiar; Auro del Giglio (Global Public Health)
Precision oncology (PO) has significantly advanced lung cancer treatment by enabling personalised therapy based on genetic mutations. However, equitable access to molecular testing and targeted therapies remains a challenge, particularly in resource-limited settings such as the Brazilian Public Health System (SUS). To identify the challenges faced by SUS in caring for patients with non-small cell lung cancer (NSCLC) in terms of access to Precision Oncology. Retrospective study with data from e-medical records of NSCLC treated between 2015–2021. 174 patients with NSCLC were included, of which 56% were females and 63% had non-squamous histology – 80% of early-stage patients and 32% of advanced-stage patients missed access to genomic testing, primarily due to short life expectancy or insufficient sample size. Only one participant underwent testing for all recommended biomarkers. Among patients with actionable mutations, 40% did not receive targeted therapy; however, regarding EGFR mutations, only 8% did not get it. Access to targeted therapy was associated with improved survival outcomes. The study highlights critical challenges and missed opportunities in the implementation of precision oncology for NSCLC management within the SUS and underscores the need for strategies to improve access to genomic testing in the public health setting.